Women are More Protected than Men against HHcy (Hyperhomocysteinemia) during their Reproductive Life: Gender-Related Differences in One- Carbon and Folate Cycles Metabolism - Clement, Arthur; Alvarez, Silvia; Jacquesson-Fournols, Laetitia; Amar, Edouard; Brami, Charles; Cornet, Dominique; Cohen, Marc; Clement, Patrice; Servy, Edouard; Elder, Kay; et al. (Archives of Clinical and Biomedical Research, 2023)
Methylation is a crucially important ubiquitous biochemical process: It relies on 2 cycles, the folates and the one carbon cycles, which activity is affected by MTHFR SNPs (Methylene TetraHydrofolate reductase, Single nucleotide polymorphisms); These SNPs affect spermatogenesis, oocyte maturation anomalies and cytologic/chromosomic anomalies. The two main MTHFR SNP variants C677T also called 677CTor c.6777C>T and A1298C also called 1298AC or c.1298A>C and homocysteine, a recognized inhibitor of methylation, have been tested in >4500 men and women suffering long lasting infertility (>3years) including repeat miscarriages and/or having failed several ART attempts with the same partner. The genetic status with highest prevalence is, for both sexes, the heterozygous C677T isoform, followed by the combined Heterozygous C677T/A1298C, and then heterozygous A1298C background. Only 14% of our population is Wild Type (WT). The T677T isoform, induces hyperhomocysteinemia (HHcy) especially in men. HHcy is always much more frequent in men. We confirm that HHCy is strongly gender related and that steroid hormones are active regulators of Hcy homeostasis. Determination of these 2 SNPs and homocysteine should not be overlooked for patients with infertility of long duration, including repeat miscarriages. Patients must also be informed about pleiotropic medical implications relevant to their own health, as well as to the health of future children (especially boys)